Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_13_19
|View full text |Cite
|
Sign up to set email alerts
|

NASA and Superalloys: A Customer, a Participant, and a Referee

Abstract: NASA has had a long history of research and development in the field of superalloys. These efforts have continued today, where the latest advancements in turbine disk and blade technologies are being developed Although NASA does support military flight systems, it's predominant role is in supporting civilian air transportation systems, and thus has goals for improving fuel efficiency, emissions, noise, and safety of today's aircraft. NASA has traditionally served several distinct but complimentary roles as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…New highly reliable life prediction systems are required as metal temperatures increase and dwell effects become dominant [2]. Fatigue and creep interactions have been the traditional failure modes considered active under dwell fatigue conditions [3].…”
Section: Introductionmentioning
confidence: 99%
“…New highly reliable life prediction systems are required as metal temperatures increase and dwell effects become dominant [2]. Fatigue and creep interactions have been the traditional failure modes considered active under dwell fatigue conditions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Heckl et al [13] concluded that with addition of 1 at-% Re the maximum application temperature can be increased by 87 K. Even an addition of 1 at-% Ru raises the limit by 38 K in low Re-containing alloys. Nevertheless concerns are rising due to the very high price of both elements, which requires careful optimization of the alloy composition [14].…”
Section: Introductionmentioning
confidence: 99%